Wintering heifer calves that are to be fattened for the summer or early fall market. - Smith, E.F.; Good, D.L.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Forty-five good quality Hereford heifer calves were purchased in south-central Kansas for use in this test. They were fed silage, prairie hay, 1 pound of protein, and 2 pounds of milo grain per head daily until the test started December 11, 1951. The 5 lightest heifers were cut off and the 40 remaining were divided into four lots of 10 heifers each.
Keywords: Beef; Fattening heifers; Bluestem pasture